Analisis Sistem Monitoring Karyawan Menggunakan Prototype dan ISO 25010 pada PT Teknologi Informatika Solusindo - Gunung Tegar Abadi; Irpan Pirmansah; Chairul Anwar (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The rapid advancement of information technology has accelerated digital transformation across various sectors to improve organizational effectiveness and operational efficiency. PT Teknologi Informatika Solusindo continues to experience challenges in monitoring employee performance due to its semi-manual monitoring process, which results in delays in data processing, a higher risk of recording errors, and limited availability of accurate information for management. This study aims to analyze system requirements and develop a web-based employee monitoring system capable of supporting more effective performance supervision. The system was developed by integrating the Prototype and Agile methodologies to produce a user-centered application through an adaptive and iterative development process. Software quality was evaluated based on the ISO/IEC 25010 international standard, covering functionality, reliability, usability, performance efficiency, compatibility, security, and maintainability. The findings demonstrate that the integrated employee monitoring system provides real-time performance data, improves data accuracy, accelerates reporting processes, and supports faster, more transparent, and data-driven managerial decision-making. Overall, the developed system contributes to enhancing operational efficiency, strengthening employee performance monitoring, and improving the effectiveness of human resource management within the company.